Exploring the factors that affect student satisfaction through using e-learning in Malaysian higher education institutions - Al-Rahmi, Waleed Mugahed (Mediterranean Center of Social and Educational Research, 2015)
In the e-learning literature, learning satisfaction with e-learning systems has been addressed. In the present study, a model and an instrument were developed to measure students’ satisfaction with e-learning systems. The study provided a description of the procedures employed in survey conceptualization, items generation, data collection and validation of multiple-item scale. It also confirmed reliability and discriminant validity of data for analysis gathered from a sample comprising 268 respondents. The researcher made use of the structural equation modeling (SEM) method with the SmartPLS program to shed a light on the adoption process. The model comprises of factors including content of e-learning, interface of e-learning, personalization of elearning, community of e-learning, self-efficacy of e-learning, perceived usefulness, perceived ease of use and intention to use e-learning and their impact on the satisfaction of students. The model was developed on the basis of technology acceptance model (TAM) and the findings evidenced that the model is a robust theoretical tool employed to examine the acceptance of elearning among students